Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Role of corneal collagen cross-linking in pseudophakic bullous keratopathy a clinico pathological study Arora R, Manudhane A, Saran RK, Goyal J, Goyal G, Gupta D Ophthalmology 2013; 120: 2413-8. Twenty – Four Hour Efficacy with Preservative Free Tafluprost Compared with Latanoprost in Patients with Primary Open Angle Glaucoma or Ocular Hypertension Konstas AGP, Quaranta L, Katsanos A, Riva I, Tsai JC, Giannopoulos T, Voudouragkaki IC, Paschalinou E, Floriani I, Haidich AB Br J Ophthalmol. 2013; 97: 1510-15. Spontaneous Vitreous Hemorrhage in Children Sudhalkar A, Chhablani J, Jalali S, Mathai A, Pathengay A Am J Ophthalmol. 2013; 156: 1267-71. Persistent Outer Retinal Fluid Following Non-Posturing Surgery for Idiopathic Macular Hole Rahman R, Oxley L, Stephenson J Br J Ophthalmol. 2013; 97: 1451-4.